9x+6(80)=7x+560

Simple and best practice solution for 9x+6(80)=7x+560 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x+6(80)=7x+560 equation:


Simplifying
9x + 6(80) = 7x + 560

Multiply 6 * 80
9x + 480 = 7x + 560

Reorder the terms:
480 + 9x = 7x + 560

Reorder the terms:
480 + 9x = 560 + 7x

Solving
480 + 9x = 560 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
480 + 9x + -7x = 560 + 7x + -7x

Combine like terms: 9x + -7x = 2x
480 + 2x = 560 + 7x + -7x

Combine like terms: 7x + -7x = 0
480 + 2x = 560 + 0
480 + 2x = 560

Add '-480' to each side of the equation.
480 + -480 + 2x = 560 + -480

Combine like terms: 480 + -480 = 0
0 + 2x = 560 + -480
2x = 560 + -480

Combine like terms: 560 + -480 = 80
2x = 80

Divide each side by '2'.
x = 40

Simplifying
x = 40

See similar equations:

| 6y=-2x | | 8x+9=9x+7 | | 6+3x+4x^2+2x^3=0 | | (6-8i)(6+8i)= | | 3(t-5)-t=7 | | 2x+2y=2809.30 | | 2(5x-6)=4[x-3x+30] | | 100x^2-21=110 | | 4(3x-9)-5=4(x-5)+27 | | 4y^3+27y^2+27=0 | | 27y^2+27=0 | | 3-4*6+3= | | 4(3x-8)-5=4(x-5)+15 | | (11x+26)-3= | | Y^6+9y^4-4y^3+27y^2+27=0 | | -7(2c+5)=(c-6) | | 8y-9=12y+15 | | 5x-(2x+4)=14 | | x^2-5x-2.25=0 | | Y=(3x+8)(x-9) | | 6+(3x-4)-(7x+11)= | | 8(7x-6)=27 | | x+20=5x+8 | | x*0.022=1 | | 12y-13=7y+12 | | 4-23=8x-6-7x | | 2(3x)+5x=770 | | 2x+11=21-3x | | 10x=20.2 | | 80=1.8+32 | | 8+2(x-8)=10-6(x-3) | | 7(x-2)+2=7x-2(2-x) |

Equations solver categories